Case report: Staged tension-reducing excision of giant acquired vulvar lymphangioma secondary to cervical cancer surgery - Hu, Ling-Juan; Fang, Hao-Ming; Lin, Huan-Mei; Kang, Xu; Lin, Ying; Xiao, Jing (Frontiers in Oncology, 2024)
IntroductionAcquired vulvar lymphangioma (AVL), a rare disease caused by the dilation of superficial lymphatic vessels secondary to deep lymphatic vessel injury, is characterized by a wide range of morphological diversity and massive exudate. This morphological heterogeneity has often led to misdiagnosis or non-diagnosis. The management of AVL presents a therapeutic challenge due to the absence of a standardized treatment protocol.Case presentationA 53-year-old female patient, previously received surgical treatments for stage IIb cervical squamous cell carcinoma, presented with vulvar enlargement and copious amount of yellow exudate seven years post-treatment. Clinically, the patient exhibited chronic vulvar swelling, with easily-exudated nodules. The vulvar biopsy revealed lymphatic vessel dilation with lymphocyte infiltration, consistent with AVL. Due to the extensive lesions and severe exudate, staged excisions of bilateral vulvar lesions were performed at one-month intervals. Follow-up examinations of this patient for one-year post-surgery showed no evidence of recurrence.ConclusionIn this instance, AVL manifest secondary to cervical cancer surgery, as a result of damage to the deep lymphatic vessels of the vulva, with characteristic symptoms of copious amounts of exudate and vulvar lesions with diverse morphologies, which provides a cautionary note for physicians. Besides, the staged resection strategy in this case may offer insights into surgical treatment protocol for extensive AVL.